Documentation of Pesticide Poisoning in Kerala and its Implications on Health and Agriculture Planning and Policy - Usha, S and Harikrishnan, V. R. (Centre for Development Studies-UPR, 2004)
This report contains two parts. One part is about developing a sustainable agriculture plan for Venganoor Panchayath, Thiruvananthapuram District and the second part is about pesticide poisoning in Kerala . The first part of the pesticide poisoning mainly focus on the pesticide accidents which happened over the last 2-3 years in Kerala, mainly those reported in the media and later on field investigations and documentation done by the researcher. It also looks into the intentional poisonings, suicides, during the period between 2003 March to 2004 February ad analyses the situation. This is based on media reports only. The study also look ed in to the statistics of Government of Kerala, to get an overall picture of the suicides in Kerala. The study has not looked into the accidents at pesticide manufacturing and formulating facilities and also those workers in the Public Health Department who do regular spraying of pesticides and fogging, due to time constraints. It is understood that State Pollution Control Board and public health department do not have a system to record cases of pesticide poisoning and this is really a barrier in formulating health policies which can help in preventing pesticide accidents . The official records generally do not tell anything about pesticide accidents although the main government hospitals like medical colleges, taluk and district hospitals cater to the needs of the people who are affected by pesticides. Every Panchayath has a hospital either in the public sector or private sector. So if there is a policy of keeping the pesticide accident records, the health department can develop a system of reporting which will help in the planning process at the local level as well as developing policy at the state level to prevent further poisonings. The second part is about planning for a sustainable ecologically based agriculture in Venganoor Panchayath, Thiruvananthapuram district. In this study main idea was to look into the existing agricultural situation in the panchayath, through secondary data, survey of selected farmers and also field study of water sources, biodiversity and agricultural diversity. Although some more in depth studies are needed based on the present assessment, a recommendation is made in the end which can be used as a guideline for the planning in the panchayath. For planning for specific input, a detailed assessment is essential.